2021
DOI: 10.1007/s40820-020-00586-z
|View full text |Cite
|
Sign up to set email alerts
|

Berlin Green Framework-Based Gas Sensor for Room-Temperature and High-Selectivity Detection of Ammonia

Abstract: Ammonia detection possesses great potential in atmosphere environmental protection, agriculture, industry, and rapid medical diagnosis. However, it still remains a great challenge to balance the sensitivity, selectivity, working temperature, and response/recovery speed. In this work, Berlin green (BG) framework is demonstrated as a highly promising sensing material for ammonia detection by both density functional theory simulation and experimental gas sensing investigation. Vacancy in BG framework offers abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…While both MAX phases have comparable Ti L‐edge profiles, it can be clearly observed that the Ti L‐edge energy of Ti 2 C 0.5 N 0.5 T x MXene moves slightly to a higher energy side compared with that of Ti 2 CT x MXene, indicating a higher average for Ti oxidation state in Ti 2 C 0.5 N 0.5 T x MXene than that of Ti 2 CT x MXene. This is consistent with the reported theoretical results showing a lower stability of carbonitrides relative to their carbide counterparts 42,43 . In addition, the bonding of TiO 2− x F x and CNTiF x are located at higher binding energy regions because of the highly electronegative from F atom 61 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…While both MAX phases have comparable Ti L‐edge profiles, it can be clearly observed that the Ti L‐edge energy of Ti 2 C 0.5 N 0.5 T x MXene moves slightly to a higher energy side compared with that of Ti 2 CT x MXene, indicating a higher average for Ti oxidation state in Ti 2 C 0.5 N 0.5 T x MXene than that of Ti 2 CT x MXene. This is consistent with the reported theoretical results showing a lower stability of carbonitrides relative to their carbide counterparts 42,43 . In addition, the bonding of TiO 2− x F x and CNTiF x are located at higher binding energy regions because of the highly electronegative from F atom 61 .…”
Section: Resultssupporting
confidence: 92%
“…To date, over 40 different MXene compositions have been reported; the vast majority of these MXenes are carbides with only a few exceptions—several nitrides and only one carbonitride ( viz ., Ti 3 CNT x ) 27 . The latter has shown distinct properties and behavior compared with Ti 3 C 2 T x in many applications including energy storage, 28–33 optics, 34,35 catalysis, 36–39 electromagnetic shielding, 40,41 sensing, 42,43 and so forth. This distinct behavior of Ti 3 CNT x compared with Ti 3 C 2 T x provides a strong motivation to develop other new carbonitrides to join the MXene family.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Zhang et al demonstrated that the Berlin green framework is a promising sensing material for ammonia detection by den- sity generalized theory simulations and experimental gas sensing studies. [18] A self-powered complete ammonia leak monitoring device was demonstrated by Feng et al [19] Yu et al prepared an organ-like Ti 3 C 2 T x MXene/metal-organic frameworkderived copper oxide (CuO) gas sensor. [20] These efforts achieve self-powered sustainable monitoring of the gas, effectively alleviating the problem of high energy consumption for the work of gas-sensitive materials.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that the Berlin green framework is a promising sensing material for ammonia detection by density generalized theory simulations and experimental gas sensing studies. [ 18 ] A self‐powered complete ammonia leak monitoring device was demonstrated by Feng et al. [ 19 ] Yu et al.…”
Section: Introductionmentioning
confidence: 99%
“…For a 3monolayer Ti 3 C 2 T x film, the specific EMI shielding effectiveness (SE/density/thickness, SSE/t) reached 2.83 × 10 6 dB• cm 2 •g −1 . 13 Ti 3 CNT x attributed to its N-doped structure, 25 sufficient surface groups, superior dimensional stability, good adhesion, and satisfactory flexibility after heat treatment has been investigated as an ideal candidate for EMI shielding. 26 However, further investigations on N-doped MXene-based composites have not been developed.…”
mentioning
confidence: 99%